Analysis of problem solving of measures of central tendency of 1st year High School students - Sousa, Amanda Cristina de (2025)
The objective of the research was to identify the strategies and difficulties of first-year high school students at a public school in teaching using the Problem-Solving approach. We used the sequence of actions proposed by Proença (2018) to conduct the class: choosing the problem, introduction, aid during resolution, discussion of strategies and articulation of strategies to content. Difficulties were assessed according to the resolution stages described by Proença (2018): representation, planning, execution and monitoring. We identified three different strategies: tree diagram, mathematical concept and guess and error, the latter being the most frequent. The main difficulties occurred in the planning stage, with only two groups presenting inappropriate approaches for the context of the problem.